Development and Characterization of Lornoxicam-Infused Ocular Gel for Effective Treatment of Ocular Inflammation in Domestic Cats - Jafer, Riyam S; J Kassab, Hanan (The Iraqi Journal of Veterinary Medicine, 2025)
Lornoxicam (LOX) is a non-steroidal anti-inflammatory drug (NSAID) effective in managing ocular inflammation. Traditional delivery methods like liquid drops are cleared rapidly and may not provide sustained therapeutic levels, necessitating the development of an ocular gel formulation. Mucoadhesive polymers such as hyaluronic acid (HA), hydroxypropyl methylcellulose (HPMC), and Carbopol have been identified as suitable excipients to modify drug release profiles. This study aims to formulate an effective ophthalmic 0.1% w/w lornoxicam gel administered to pets for topical and continuous drug release, enhancing therapeutic efficacy while minimizing possible side effects. Eight formulations of lornoxicam ocular gel were developed by different concentrations of hyaluronic acid (HA) and hydroxypropyl methylcellulose (HPMC K100) with 0.5% w/v Carbopol P934. These formulations were in vitro evaluated for viscosity, spreadability, and drug release characteristics to the best formula G6. The formulation with optimal performance was G6 (0.5% w/v Hyaluronic acid). Ocular irritation testing was performed to assess the safety and tolerability of the formulation using a Rattus norvegicus Domestica (domestic Norwegian rat) model. Furthermore, the therapeutic potential of the lornoxicam gel was investigated in a domestic cat case study, demonstrating its efficacy in treating ocular inflammation resulting from traumatic eye injury. The optimized formula G6 formulation 0.5% w/v demonstrated appropriate viscosity and spreadability, making it suitable for ocular administration. In vitro release, studies revealed an initial burst release of 92.5% within the first two hours, followed by a sustained release over the subsequent 6 hours. Ocular irritation testing using a rat model confirmed that the lornoxicam ocular gel was non-irritating. Furthermore, the therapeutic effects of the gel were observed in domestic cats, with notable improvements in ocular conditions, including reduced swelling, redness, and dryness, for less than 7 days of treatment. The lornoxicam ocular gel demonstrates promising characteristics for safe and effective treatment of ocular inflammation in domestic cats‎‎‎.